Irritable bowel syndrome – a literature review - Cuber, Iwona; Aghadi, Artur; Białowąs, Edyta; Dybała, Ewelina; Mazurek, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction: Irritable bowel syndrome (IBS) is one of the most common diseases affecting people around the world. It is characterized by irregular bowel movements and abdominal pain. IBS significantly reduces the quality of life of patients. Despite such a frequent occurrence of this disease, its correct diagnosis and treatment still causes many problems for primary care physicians. Aim of the study: The aim of the study is to present the current state of knowledge on the pathophysiology, diagnostics and drugs used in irritable bowel syndrome. Description of the state of knowledge: Many factors may play a role in the pathogenesis of IBS. The most common are: genetic factors, intestinal motility disorders, visceral hypersensitivity, mental disorders, especially disorders of the brain-gut axis regulation, past intestinal infections, intestinal microbiota disorders and food intolerances. The Rome IV criteria are currently used in the diagnosis of IBS. Treatment of irritable bowel syndrome includes lifestyle modification and dietary management, pharmacotherapy and psychotherapy. Summary: Irritable bowel syndrome is a chronic disease, symptoms often recur and complete recovery is not possible.